2023
DOI: 10.1002/adfm.202212233
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Mismatch Substitution in Layered Double Hydroxides as Efficient Oxygen Electrocatalysts for Flexible Zinc–Air Batteries

Abstract: Although layered double hydroxides (LDHs) are extensively investigated for oxygen electrocatalysis, their development is hampered by their limited active sites and sluggish reaction kinetics. Here, sulfur mismatch substitution of NiFe-LDH (S-LDH) is demonstrated, which are in-situ deposited on nitrogen-doped graphene (S-LDH/NG). This atomic-level sulfur incorporation leads to the construction of the tailored topological microstructure and the modulated electronic structure for the improved catalytic activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…PDOS of the two interfaces is also analyzed to investigate the contribution of each atomic orbital to the DOS. [ 42 ] As shown in Figure S5 (Supporting Information), the orbital p dominates the interfacial molecular interaction of Al(1 1 1)‐H 2 O and Al(1 1 1)‐PB interface. Moreover, the strength of atomic bonding by the orbital p in the Al(1 1 1)‐PB interface is higher than Al(1 1 1)‐H 2 O due to the larger pseudogap value of 0.113 Ha for the former interface, as shown in Figure 5c.…”
Section: Resultsmentioning
confidence: 99%
“…PDOS of the two interfaces is also analyzed to investigate the contribution of each atomic orbital to the DOS. [ 42 ] As shown in Figure S5 (Supporting Information), the orbital p dominates the interfacial molecular interaction of Al(1 1 1)‐H 2 O and Al(1 1 1)‐PB interface. Moreover, the strength of atomic bonding by the orbital p in the Al(1 1 1)‐PB interface is higher than Al(1 1 1)‐H 2 O due to the larger pseudogap value of 0.113 Ha for the former interface, as shown in Figure 5c.…”
Section: Resultsmentioning
confidence: 99%
“…To further improve the oxygen catalytic activity, Han et al demonstrated that S-incorporated NiFe-LDH on N-doped graphene (S-LDH/NG) acted as bifunctional oxygen electrocatalyst for rechargeable ZABs. 157 The mismatch substitution of introduced S species led to a tailored topological microstructure and optimized electronic structure for boosting the activity and durability. Consequently, the as-fabricated ZABs with the S-LDH/NG cathode achieved a high P max of 165 mW cm −2 , large energy density of 772 W h kg −1 , and long cycle stability of 120 h. Yu et al tuned the proportion and valence state of metal ions in Ni–Fe–Co oxide/hydroxide to significantly modify its electronic structure.…”
Section: Air Cathodesmentioning
confidence: 99%
“…But the chemistry of materials with inherent limitations makes it difficult to meet the growing needs. [1][2][3][4][5][6][7] Electrochemical redox reactions such as the oxygen reduction reaction (ORR), 8,9 oxygen evolution reaction (OER), 10,11 and hydrogen evolution reaction (HER) 12,13 occur at the electrodes of these devices. The electrocatalyst should promote the ORR in fuel cells, OER in metal-air batteries, and HER for dihydrogen fuel generation.…”
Section: Introductionmentioning
confidence: 99%